EXPLORING LATENT DETERMINANTS OF ENTERPRISE OCCURRENCES IN PLANNED RESIDENTIAL AREAS (Jurnal Kemanusiaan, 2017)
ABSTRACT Home-based enterprises, an informal sector engagement in emerging economies are usually identified with informal neighbourhoods characterised by low householdsâ€™ income. The occurrence of HBEs in formal middle-income neighbourhoods requires investigation. The exploration of the extent to which latent factors led to this development inspired a study of planned residential areas of Lokoja, Kogi state, Nigeria. Cluster sampling of ten neighbourhoods using specific criteria was adopted to select the study areas and 353 questionnaires structured on Likertâ€™s scale were administered to the entire population of HBE operators in the study areas. Confirmatory factor analysisÂ (CFA) through structural equation modelling of â€œaspiration vectorsâ€ indicates satisfactory goodness of fit among accepted determinants of the model. This is an indication that other than income generation motives emphasised in previous studies, other latent factors are also significant determinants of HBE occurrences. Mixed-use strategies has been suggested as a way of integrating living and economic activities.